Monoclonal Antibodies against the Human Mannose Receptor that Inhibit the Binding of Tissue-type Plasminogen Activator - Barrett-Bergshoeff, Marrie; Noorman, Femke; Bos, Rogier; Rijken, Dingeman C (Thrombosis and Haemostasis, 1997)
To study the role of the mannose receptor in cellular uptake and degradation of tissue-type plasminogen activator (t-PA), a set of five monoclonal antibodies (Moab) was generated against the mannose receptor isolated from human placental tissue.All Moab specifically recognised the 175 kDa mannose receptor in a crude placenta extract, as shown in Western blot analysis. By use of im- munohistochemistry, we showed that in human placenta only the Hof- bauer cells (fetal macrophages) express the mannose receptor. Epitope competition experiments indicated that the Moab bound to at least two different epitopes on the receptor molecule. Moab 14-3, 14-5, and 15-2, which are directed against one of these epitopes, strongly inhibited the interaction between the purified mannose receptor and t-PA. These Moab also inhibited mannose receptor-mediated degradation of t-PA by cultured human macrophages. The low density lipoprotein receptor-related protein (LRP) mediated t-PA degradation was not affected by the Moab.It is concluded that the Moab are useful for studying the expression of the human mannose receptor in Western blot and in immunohisto-chemistry, and for studying the interactions between the human mannose receptor and the mannose-containing ligand t-PA.